(untitled) (Journal of Computational Mathematics, 2021)
A new mixed Legendre-Hermite interpolation is introduced. Some approximation results are established. Mixed Legendre-Hermite pseudospectral method is proposed for non-isotropic heat transfer in an infinite plate. Its convergence is proved. Numerical results show the efficiency of this approach.